In vitro apical extrusion of debris and instrumentation time following root canal instrumentation with Reciproc and Reciproc Blue instruments and a novel stainless steel rotary system (Gentlefile) versus manual instrumentation - Ahmad Nouroloyouni; Shahriar Shahi; Amin Salem Milani; Sara Noorolouny; Robab Farhang; Aysan Yousefi Azar (Tabriz University of Medical Sciences, 2023)
Background. This study compared apical extrusion of debris and instrumentation time following root canal instrumentation with Reciproc, Reciproc Blue, and Gentlefile (GF) rotary instruments versus the manual step-back technique. Methods. This in vitro study was conducted on 80 extracted mandibular premolars with mature apices and a root curvature of<10º. The teeth were randomly assigned to 4 groups (n=20), standardized regarding working length, and placed in pre-weighed vials. The root canals were instrumented with Reciproc, Reciproc Blue, and GF systems and the manual step-back technique in the four groups. The vials containing the collected debris were then dried and weighed. The instrumentation time was also recorded for each group. Data were analyzed with one-way ANOVA and post hoc Games-Howell test (α=0.05). Results. Minimum apical debris extrusion was noted in Reciproc, followed by Reciproc Blue, GF, and manual technique (P<0.05). Pairwise comparisons showed significantly lower apical extrusion of debris in the Reciproc compared with GF (P=0.015) and manual instrumentation (P=0.011) groups. The Reciproc system also had the shortest instrumentation time, followed by Reciproc Blue, GF, and manual instrumentation (P<0.05). Pairwise comparisons showed significant differences between all the systems (P<0.05) except between Reciproc and Reciproc Blue (P>0.05) in this respect. Conclusion. Although all systems caused apical extrusion of debris, manual instrumentation caused maximum extrusion of debris. In contrast, the Reciproc system was superior to others regarding minimal apical extrusion of debris and the shortest instrumentation time.